2021
DOI: 10.1002/cptc.202000285
|View full text |Cite
|
Sign up to set email alerts
|

Photomodulation of a Dual‐Color Luminescent System Combining Quantum Dots with a FRET Acceptor Ligand**

Abstract: Herein, we report on a dual-color, photoswitchable donoracceptor nanosystem based on quantum dots (QD) and an anthryl quinolyl ethylene photoactive functional ligand (AQE-FL), in which a carboxylic group is used to anchor AQE-FL to QD. Photophysical and photochemical properties of the resulting photoswitchable QD system (psQD) were studied by steady state and time-resolved spectroscopic methods. Efficient Förster resonance energy transfer (FRET) from QD to AQE-FL was shown. Applicability of the Stern-Volmer fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…We note that such a high multicolor switching ratio has been rarely achieved in the reported multi-color uorescence photoswitchable nanoprobes. 36,[53][54][55][56] Previous studies found that uorescent switches fabricated by noncovalently conjugating the uorescence donor with the photochromic acceptor are more favorable for achieving a high switching ratio than that constructed by covalent binding. [57][58][59][60] Thus, instead of covalent conjugation, we adopted a rather mild strategy by physically encapsulating both AuNCs and spiropyran inside lipid NPs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We note that such a high multicolor switching ratio has been rarely achieved in the reported multi-color uorescence photoswitchable nanoprobes. 36,[53][54][55][56] Previous studies found that uorescent switches fabricated by noncovalently conjugating the uorescence donor with the photochromic acceptor are more favorable for achieving a high switching ratio than that constructed by covalent binding. [57][58][59][60] Thus, instead of covalent conjugation, we adopted a rather mild strategy by physically encapsulating both AuNCs and spiropyran inside lipid NPs.…”
Section: Resultsmentioning
confidence: 99%
“…So far, a variety of nanoparticles have been used to construct photocontrolled uorescence switches, such as semiconductor quantum dots, 31 upconverting NPs, 32 perovskite nanocrystals 33 and metal nanoclusters. 34 However, multi-color uorescence photoswitches based on ligand-protected NPs have rarely been achieved, [34][35][36] and the distinct capability of NPs for modulating the photophysical properties of photochromic dyes has not been adequately exploited. 6,37,38 Photoisomerization kinetics of photochromic compounds is regarded as an important issue in determining their performance in applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation